2017
DOI: 10.1002/jmv.24809
|View full text |Cite
|
Sign up to set email alerts
|

SB 9200, a novel agonist of innate immunity, shows potent antiviral activity against resistant HCV variants

Abstract: SB 9200 is a novel, first-in-class oral modulator of innate immunity that is believed to act via the activation of the RIG-I and NOD2 pathways. SB 9200 has broad-spectrum antiviral activity against RNA viruses including hepatitis C virus (HCV), norovirus, respiratory syncytial virus and influenza and has demonstrated activity against hepatitis B virus (HBV) in vitro and in vivo. In phase I clinical trials in chronically infected HCV patients, SB 9200 has been shown to reduce HCV RNA by up to 1.9 log10. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…These drugs, however, may cause side effects such as lactic acidosis and possible liver, and kidney failure. SB9200 is effective for HCV patients with relapse after DAA and interferon treatment and could serve as a promising treatment option for patients who are not responding to the current regimen of DAA therapy ( 52 ). The phase 1 clinical trial on naïve adult with chronic hepatitis C showed an association between the decline in viral RNA and the peak of SB9200 detection in plasma (Clinical trial no NCT01803308).…”
Section: Nucleotide-based Antiviralsmentioning
confidence: 99%
“…These drugs, however, may cause side effects such as lactic acidosis and possible liver, and kidney failure. SB9200 is effective for HCV patients with relapse after DAA and interferon treatment and could serve as a promising treatment option for patients who are not responding to the current regimen of DAA therapy ( 52 ). The phase 1 clinical trial on naïve adult with chronic hepatitis C showed an association between the decline in viral RNA and the peak of SB9200 detection in plasma (Clinical trial no NCT01803308).…”
Section: Nucleotide-based Antiviralsmentioning
confidence: 99%
“… 83 , 84 Indeed, the antiviral SB 9200, a novel first-in-class oral modulator of innate immunity with a broad-spectrum activity in vitro and in vivo against RNA viruses including hepatitis C virus, norovirus, respiratory syncytial virus and hepatitis B virus, is also believed to act via NOD2 pathway. 85 Furthermore, infection with human cytomegalovirus results in significant induction of NOD2 expression, activating downstream NF-κB and IFN pathways. 84 Besides, following recognition of a viral ssRNA genome, NOD2 uses the adaptor mitochondrial antiviral signaling protein to activate IRF3; interestingly, NOD2-deficient mice fail to produce IFN efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…A pre-clinical compound specific for RIG-I is RGT100 (Merck/Rigontec), currently in phase I clinical trials for treatment of advanced solid tumors and lymphomas (NCT03065023), although peer-reviewed preclinical reports for RGT100 were not identified, to our knowledge. Another compound which activates RIG-I by unknown mechanisms is SB-9200 [ 78 ], which is currently under investigation as an anti-viral agent, but has not yet been tested in the pre-clinical setting of cancer treatment.…”
Section: Introductionmentioning
confidence: 99%